Impaired oesophageal transit of capsule versus tablet formulations in the elderly. - Perkins, A C (1994)
Drug induced oesophageal injury is an important and preventable cause of iatrogenic injury. In most cases the injury is considered to be due to mucosal contact from formulations lodged in the oesophagus. A scintigraphic study was performed comparing the oesophageal transit of enteric coated tablets with similar sized and shaped gelatin capsules, using a population of elderly healthy volunteers similar in age (50-79 years) to the population most likely to be receiving regular treatment. Twenty three volunteers injected the radiolabelled tablet or capsule with 50 ml of water while sitting on two separate occasions according to a randomisation schedule. Oesophageal transit was assessed by gamma scintigraphy. Gastric residence was also assessed in 11 of 23 subjects. While the tablet was readily cleared from the oesophagus, mean transit time 4.3 seconds (range 1.0-14.0), the capsule often showed a comparatively prolonged holdup, mean transit time 20.9 seconds (range 1.5-174.5). Ten of 11 tablets emptied from the stomach intact, while all 11 capsules broke up in the stomach. Gelatin capsules showed a clear tendency to remain within the oesophagus of healthy elderly volunteers, while similar sized enteric coated tablets did not. These studies show the importance of assessing oesophageal transit when designing the formulation of drugs with a potential for oesophageal injury.